2018
DOI: 10.1155/2018/8436749
|View full text |Cite
|
Sign up to set email alerts
|

Nondrainage after Laparoscopic Cholecystectomy for Acute Calculous Cholecystitis Does Not Increase the Postoperative Morbidity

Abstract: Background It is now established that prophylactic drainage is not needed after laparoscopic cholecystectomy (LC) for chronic calculous cholecystitis. However, the benefit of drains versus their potential harm for acute calculous cholecystitis (ACC) following laparoscopic LC has been questioned. Therefore, we conducted a comparative study to assess the need for drainage. Methods Between January 2014 and October 2016, 212 patients with ACC undergoing LC undergo either drainage (n= 106) or no drainage (n= 106). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
9
1
Order By: Relevance
“…This aspect finds confirmation in Lewis et al (37), who showed that no patient without surgical drain required reoperation or subsequent drainage procedure for subhepatic collections formation, as well as no difference in the frequency of wound infections. However, in other studies, such correlations are not confirmed with the statistical consistency (5,20). As a result of our study, patients undergoing LC with surgical drain placement have a longer length of hospital stay than those without the placement of this device, as confirmed in previous studies (5,6).…”
Section: Discussioncontrasting
confidence: 43%
“…This aspect finds confirmation in Lewis et al (37), who showed that no patient without surgical drain required reoperation or subsequent drainage procedure for subhepatic collections formation, as well as no difference in the frequency of wound infections. However, in other studies, such correlations are not confirmed with the statistical consistency (5,20). As a result of our study, patients undergoing LC with surgical drain placement have a longer length of hospital stay than those without the placement of this device, as confirmed in previous studies (5,6).…”
Section: Discussioncontrasting
confidence: 43%
“…An increased incidence of drain insertion with age was well correlated with the severity of acute cholecystitis in the elderly. This could also be an explanation for the increased incidence of postoperative septic complications, such as wound infection and intra-abdominal collections, described by other authors [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 67%
“…A recent meta-analysis has condemned its routine usage of intra-abdominal drainage tube 19. Most of the studies have failed to demonstrate the benefit of placing drainage tube routinely 1920. This is probably due to a very low incidence of complications.…”
Section: Discussionmentioning
confidence: 99%